2020
DOI: 10.1111/echo.14561
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the prognostic significance of low gradient severe aortic stenosis and preserved left ventricular function requires the integration of the consistency of stroke volume calculation and clinical data

Abstract: Background:This study was to evaluate the prognostic significance of low gradient severe aortic stenosis (LG SAS) and preserved left ventricular ejection fraction (LVEF) with the integration of echocardiographic and clinical data. Methods:The study included 172 patients with LG SAS (AVAi ≤ 0.6 cm 2 /m 2 , mean aortic pressure gradient < 40 mm Hg) and LVEF (≥ 50%). LV outflow tract diameters were measured at both the aortic valve annulus and 5 mm below the annulus for the measurement consistency. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…We used multi-LVOT diameter measurements to address the importance of consistency of SV calculation for an AS outcome study. 4 Both Guzzetti et al and our studies showed three types of LVOT shapes. However, the percentages of each type vary with patient selections.…”
Section: Of Distancessupporting
confidence: 56%
See 1 more Smart Citation
“…We used multi-LVOT diameter measurements to address the importance of consistency of SV calculation for an AS outcome study. 4 Both Guzzetti et al and our studies showed three types of LVOT shapes. However, the percentages of each type vary with patient selections.…”
Section: Of Distancessupporting
confidence: 56%
“…The distance from the coaptation point perpendicular to the interventricular septum, also known as the ''C-sept'' distance, has also emerged as an independent risk factor for SAM and LVOTobstruction after MV repair, 2,3 as well as after surgical or transcatheter aortic valve replacement 4,5 and in patients with hypertrophic cardiomyopathy. 6 While the description of methodology of C-sept measurement is incomplete in some of these studies, Maslow et al, 2 in their seminal study that has identified C-sept < 2.5 cm as an independent risk factor for SAM after MV repair, describe the measurement as performed in early systole.…”
Section: Of Distancesmentioning
confidence: 99%
“…A recent study showed that AVA impacts prognosis only in those with high-gradient AS and preserved LVEF and whether AVA truly adds prognostic information over V max or MPG is not clear in patients with LG SAS [ 34 ]. Although different theories and explanations have been proposed, the inherent variability in calculating SV by echocardiography may have a significant impact on the accuracy in diagnosing true SAS and/or classifying flow state in some patients [ 16 , 35 ]. With the limitations of echocardiography in determining the true severity of AS based on AVA and in the absence of a high pressure gradient, conservative management of LG SAS patients with low EuroSCORE II may be considered as an option in a medium-term with close follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…With such a discrepancy in natural history, the choice of treatment of LG SAS needs further investigation [ 15 ]. Our prior study showed echocardiographic and clinical characteristics may play a role in prediction of prognosis in low-gradient AS [ 16 ]. Therefore, we hypothesized that clinical outcome in patients with LG SAS and preserved LVEF may be associated with multiple risk factors, comorbidities and certain echocardiographic features.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Prior studies have reported that LFS was associated with unfavorable outcomes in patients with low-flow severe AS. [4][5][6][7][8] Although a high prevalence of low-flow, lowgradient AS (approximately 30%) has been reported for decades, the prevalence of LFS in populations without valvular disease has not been systematically investigated. Traditionally, the pathophysiology of LFS has been often attributed to LV dysfunction leading to low SV.…”
mentioning
confidence: 99%